Immobilization of recombinant Escherichia coli on multi-walled carbon nanotubes for xylitol production - Noor Hidayah, Abd Rahman; Jamaliah, Md. Jahim; Mimi Sakinah, A. M.; Roshanida, A. Rahman; Siti Fatimah Zaharah, Fuzi; Rosli Md, Illias (Elsevier, 2020)
E. coli has been engineered to produce xylitol, but the production faces bottlenecks in terms of production yield and cell viability. In this study, recombinant E. coli (rE. coli) was immobilized on untreated and treated multiwalled carbon nanotubes (MWCNTs) for xylitol production. The immobilized rE. coli on untreated MWCNTs gave the highest xylitol production (5.47 g L−1) and a productivity of 0.22 g L−1 h−1. The doubling time for the immobilized cells increased up to 20.40 h and was higher than that of free cells (3.67 h). Cell lysis of the immobilized cells was reduced by up to 73 %, and plasmid stability improved by up to 17 % compared to those of free cells. Xylitol production using the optimum parameters (pH 7.4, 0.005 mM and 29 °C) achieved a xylitol production and productivity of 6.33 g L−1 and 0.26 g L−1 h−1, respectively. A seven-cycle repeated batch fermentation was carried out for up to 168 h, which showed maximum xylitol production of 7.36 g L−1 during the third cycle. Hence, this new adsorption immobilization system using MWCNTs is an alternative to improve the production of xylitol.